The Mycobacterium tuberculosis cytochrome bcc:aa3 cryo-EM structure and discovery of novel putative cytochrome bcc:aa3 inhibitors - Mathiyazakan, Vikneswaran (Nanyang Technological University, 2023)
Tuberculosis is the second leading cause of death caused by a single causative agent. The M. tuberculosis oxidative phosphorylation (OXPHOS) pathway terminal oxidases cyt-bcc:aa3 and cyt-bd were successfully targeted by Telacebec and ND-011992 respectively. The interest to understand the M. tuberculosis cyt-bcc:aa3 led to the purification of the supercomplex with a bound sodC superoxide dismutase. The cryo-EM structure of the supercomplex was resolved at 4.5 Å resolution. The structure provides insights into the electron transfer pathways and further understanding on drug interaction with the enzyme complex. A whole cell library screen targeting cyt-bcc:aa3 identified hits that depleted whole cell ATP levels, inhibited growth and dramatically decreased oxygen consumption rate in real-time. An in silico campaign targeting the QcrC subunit of cyt-bcc:aa3 yielded a hit that reduced ATP levels in inverted membrane vesicles and affected electron transfer in cyt-bcc:aa3. Lastly, the influence of sodC against OXPHOS targeting compounds were evaluated.